MENINGKATKAN AKTIVITAS BELAJAR SISWA DENGAN MODEL PEMBELAJARAN INKUIRI PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) DI KELAS V-A SD NEGERI 101775 SAMPALI - Wesly Silalahi; Syahira Dana Nasution (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The purpose of this study was to find out how to improve student learning activities with Inquiry learning models in Natural Sciences (IPA) subjects. The method of this research is Classroom Action Research (CAR) with the subject of all students of class V-A SD Negeri 101775 Sampali which amounted to 31 students. By observing student learning activities, in Cycle I of 1st Meeting there were 9 active students with a percentage of 32.26%. In Meeting Cycle I there were 16 active students with a percentage of 51.61%. Furthermore, there was a good increase in Cycle II of Meeting 1. There were 25 active students with a percentage of 80.65% and in Cycle II the 2nd Meeting became 90.32% with many active students, 28 students. While the results of questionnaires showed that in Cycle I, there were 16 students classified as active with a percentage of 51.61%, then in Cycle II it rose to 28 students with a percentage of 90.32%. From these results it can be said that this study was successful. Keywords: Learning activities, Science subjects, Inquiry learning models